A Bibliometric Analysis of Cyclophosphamide, Methotrexate, and Fluorouracil Breast Cancer Treatments: Implication for the Role of Inflammation in Cognitive Dysfunction - Corley, Christa; Allen, Antiño R. (Frontiers in Molecular Biosciences, 2021)
Inflammation is considered one of the possible mechanisms behind long-term cognitive dysfunction persistent after chemotherapy treatment. The chemotherapy combination of cyclophosphamide, methotrexate, and fluorouracil (CMF) was one of the older methods of treating breast cancer patients. Decades later, these patients still report experiencing cognitive side effects. In this present bibliometric review, we applied the VOSviewer tool to describe the existing landscape on literature concerning inflammation as it relates to CMF and cognitive dysfunctions. As time progressed, we saw an increase in interest in the topic. By the mid-2010s there was approximately 1,000 publications per year. Terms related to brain and CNS did not appear until the latter years, and terms related to inflammation and breast cancer were very prevalent throughout the three decades. Also, in the more recent years, inflammatory markers and plant derived compounds used to alleviate side effects of the inflammatory response appeared in the search results. The USA remained the most prolific producer of CMF-, inflammation-, and cognitive dysfunction-related papers throughout the three decades followed by Asia and Europe. As research of cognitive dysfunction caused by inflammation due to chemotherapy treatment progresses, more opportunities emerge for therapeutic methods to improve the quality of life for long term survivors